Protibakterijske spojine z multiplim delovanjem - Durcik, Martina (Farmacevtski vestnik, 2022)
The discovery of antibiotics, the so-called »wonder drugs«, contributed significantly to the reduction of mortality rates and had a positive impact on medical progress. After the introduction of antibiotics, bacteria started to develop various mechanisms of resistance, and so increasing bacterial resistance to known antibacterial agents is a global problem in the 21st century. Bacteria can develop resistance to all known antimicrobials, and despite a large number of studies and many compounds in clinical trials, the need to discover new active ingredients and therapeutic approaches is growing. Compounds that inhibit multiple bacterial targets, known as multitarget ligands, are one of the strategies to fight bacterial resistance. Simultaneous inhibition of multiple targets in bacteria means that mutations leading to resistance should originate in several sites at the same time, which is less likely. Although multiple-acting compounds do not represent an absolute solution, they can contribute significantly to slowing down the emergence of resistant strains.
Keywords: bakterijska odpornost; Bakterijska rezistenca; konjugati; multipli zaviralci; protibakterijske spojine